2012
DOI: 10.1097/dad.0b013e3181ed39f9
|View full text |Cite
|
Sign up to set email alerts
|

p53 Staining Correlates With Tumor Type and Location in Sebaceous Neoplasms

Abstract: Sebaceous neoplasms are commonly considered in their relationship to the Muir-Torre Syndrome and the now well-documented loss of DNA mismatch repair proteins leading to microsatellite instability. However, sebaceous neoplasms showing microsatellite instability comprise only a subset of this group of tumors, and thus alternative tumorigenic mechanisms must exist. This paper explores the relationship of p53, a tumor suppressor implicated in other cutaneous malignancies, and sebaceous neoplasia. We examined 94 se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 40 publications
4
34
1
Order By: Relevance
“…The present study is in general agreement with work by Jakobiec, Kiyosaki, and Shalin [7,8,37]. Strong nuclear p53 staining was observed in SC in contrast to the sebaceous hyperplasia, sebaceous adenomas, and epithelioma.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The present study is in general agreement with work by Jakobiec, Kiyosaki, and Shalin [7,8,37]. Strong nuclear p53 staining was observed in SC in contrast to the sebaceous hyperplasia, sebaceous adenomas, and epithelioma.…”
Section: Discussionsupporting
confidence: 82%
“…While similar frequencies of p53 mutations have been found in both low-grade and high-stage SC, no significant correlation has been established between the severity of p53 mutation and tumor size, recurrence, metastasis, pagetoid spread, or location [36]. Recent work by Shalin et al has shown significant differences in staining between malignant SC and benign lesions [37]. Similarly demonstrating the genetic to tumor association, a report of a patient with Li-Fraumeni syndromeharboring a germ-line TP53 mutation-was recently reported to have SC [38].…”
Section: Genetic Featuresmentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings are largely concordant with prior publications, although earlier studies were smaller and did not specifically examine or report on intraepithelial tumor cells. With respect to p53, immunoreactivity has been reported in 8/15 SC cases (53%) [4], 17/17 cases (100%) [5], 22/42 cases (52%) [6], 4/10 cases (40%) [7] and 4/8 cases (50%) [8]. The combined incidence of p53 expression in these prior studies (55/92; 60%) is relatively similar to the 63% with moderate or strong immunoreactivity which we identified in the main tumor masses.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Nuclear p53 staining was found to be significantly associated with the diagnosis of sebaceous carcinoma compared with benign sebaceous lesions. 32 Trichofolliculoma.-To date, vulvar trichofolliculoma in the literature is limited to a single series citing 3 cases. 33 All 3 were associated with vulvar intraepithelial neoplasia.…”
Section: Folliculosebaceousmentioning
confidence: 99%